Temperature and time induced assembly phase changes of engineered spidroin protein solutions - Tolmachev, Dmitry; Tunn, Isabell; Harmat, Adam L.; Möttönen, Nea B.; Scacchi, Alberto; Linder, Markus B.; Sammalkorpi, Maria (Elsevier BV, 2026)
Here, we explore the molecular level origins of the curious temperature and time dependent assembly phase response of silk-like protein materials. Combining molecular dynamics simulations, CD and FTIR spectroscopy, as well as optical microscopy, we examine the assembly phase response of model engineered tri-block protein constructs with a middle intrinsically disordered region and folded terminal domains. We show that, the assembly phase response over a broad temperature range between 20 and 80 °C arises from strong interprotein interactions. The phase transitions are governed by the interplay of changes in the entropy of the flexible glycine-rich regions and the hydrophobic interactions between the α-helices rich in alanine (Ala). Furthermore, we observe irreversible gelation at high temperatures and during aging (time-induced gelation). Thermal gelation rises via interactions between the Ala-rich regions and subsequent formation of β-sheets that crosslink the protein network. On the other hand, the time-induced gel is formed with no notable secondary structure transitions of the middle block via percolation of the protein, which is sensitive to the dimerizing interactions of the terminal domains. Overall, the significance of this work is that we identify time as a separate design variable from the molecular level characteristics and solution conditions of the silk-like protein gels, and extract assembly guidelines for the gel formation and its characteristics.